The Influence Of Principal Leadership In Improving Teacher Performance Through Motivation At Smpn Pasangkayu District - choiriah; Muhammad Rusydi; Ahmad AC (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of principal leadership on teacher performance through work motivation at public junior high schools in Pasangkayu Regency. The approach used was quantitative, with data collected through questionnaires distributed to 100 teachers from four schools: Public Junior High School 1 Pasangkayu, Public Junior High School 1 Bambalamotu, Public Junior High School 1 Bambaira, and Public Junior High School 4 Pasangkayu. Data analysis was conducted using the Structural Equation Modeling (SEM) method to test the direct and indirect effects between variables. The results of the study indicate that principal leadership has a positive and significant effect on teacher work motivation. Work motivation also has a positive and significant effect on teacher performance. Furthermore, principal leadership does not have a direct positive and significant effect on teacher performance, but it does have a positive and significant effect through work motivation as a mediating variable. These findings emphasize the importance of implementing a leadership style that supports, trains, and provides trust to teachers to improve their motivation and performance